THE INFLUENCE OF LOGICAL THINKING ON THE ABILITY TO MANIPULATE RHYTHMIC GYMNASTICS APPARATUS IN ELITE ATHLETES - Anca Maria SABĂU; Lissa Carina BĂLĂȘOIU; Andrada Maria BULZ; Dana Ioana CRISTEA (GeoSport for Society)
Rhythmic gymnastics, a distinguished discipline within the Olympic sports family, exemplifies a sophisticated blend of athleticism and artistic expression, categorizing it as a technicalcombinatory sport where precise motor control is paramount. This study investigates the relationship between academic performance in subjects requiring logical and mathematical reasoning and the proficiency of gymnasts in handling rhythmic gymnastics apparatus. Through the analysis of statistical data and mathematical assessments, the research aims to determine the impact of mathematical skills on executing complex and high-risk elements in rhythmic gymnastics routines. The findings reveal a significant correlation between mathematical test scores and gymnasts' performance, indicating that cognitive abilities in logical and mathematical reasoning substantially enhance the athletes' capability to perform intricate maneuvers with precision and control. This suggests that success in rhythmic gymnastics is not solely dependent on physical attributes but is also significantly influenced by cognitive skills. These results underscore the importance of integrating cognitive training into athletic preparation to achieve excellence in rhythmic gymnastics.